Manejo emocional y acción colectiva: las emociones en la arena de la lucha política - Gravante, Tommaso; Poma, Alice (El Colegio de México, 2018)
The article provides an analysis of three emotion management strategies in collective action. From the analysis of in-depth interviews with a Mexican group that is defending a forest, we will present the role of emotion management to avoid activists’ burnout. This article will analyze the management of fears, which has found greater attention in the analysis of collective action in repressive contexts, but also how the subjects handle powerlessness and hopelessness. The aim of this paper is to contribute to understanding the role of emotion management in social movements, showing how emotions are central elements in the arena of political struggle.